Analisis Pengaruh Pertumbuhan Ekonomi dan Upah Minimum terhadap Penyerapan Tenaga Kerja di Kabupaten Malang - Rusniati, Ririn; Sudarti, Sudarti; Agustin, Atut Frida (Falah: Jurnal Ekonomi Syariah, 2018)
The purpose of this study is to determine the effect of economic growth and minimum wage on labor absorption at Malang Regency in 2002-2016. The method of analysis used in this research is multiple linear regression. The results showed that economic growth had a positive and significant effect on labor absorption in Malang Regency in 2002-2016 with t value (3.54)> t table (1,79588) and significant value 0,0041 (below 5%) . Based on the results of these studies can be taken information that the higher economic growth hence the absorption of labor will increase. Minimum wage has negative and insignificant effect on labor absorption in Malang Regency in 2002-2016 with t value (-0.42) <t table (1,79588) and significant value 0,6792 (above 5%). Based on the results of this study can be taken information that the higher minimum wage will lead to reduced absorption of labor in Malang regency. Economic growth and minimum wages have a significant effect simultaneously on the absorption of manpower in Malang district in 2002-2016. This is indicated by the value of F arithmetic (6.44)> F table (3.59) with significant value of 0.012553.